2018
DOI: 10.1186/s13002-018-0248-1
|View full text |Cite
|
Sign up to set email alerts
|

Traditional knowledge of wild edible plants with special emphasis on medicinal uses in Southern Shan State, Myanmar

Abstract: BackgroundMyanmar is one of the hotspots of biodiversity and is a rapidly developing country. Performing floristic research in Myanmar is an urgent issue, and ethnobotanical studies of wild edible plants (WEPs) will provide new information on natural plant resources.MethodEthnobotanical data were collected in three villages with different historical backgrounds in Southern Shan State, Myanmar. A total of 19 key informants were interviewed, and specimens were collected in the fields with the participation of ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
58
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 35 publications
0
58
1
Order By: Relevance
“…Medicinal Plant List of Myanmar , a book published by FAME Company in Myanmar, recorded more than 1500 medicinal plant species [ 2 ]. Few ethnobotanical studies documented various list of medicinal plants used locally such as in southern Shan State [ 3 ], at Natma Taung National Park [ 4 ], and in southern Chin State [ 5 ]. These publications provide pilot investigations and fundamental information to understand the value of these wealthy biodiversity and culture for medicinal plants in Myanmar.…”
Section: Introductionmentioning
confidence: 99%
“…Medicinal Plant List of Myanmar , a book published by FAME Company in Myanmar, recorded more than 1500 medicinal plant species [ 2 ]. Few ethnobotanical studies documented various list of medicinal plants used locally such as in southern Shan State [ 3 ], at Natma Taung National Park [ 4 ], and in southern Chin State [ 5 ]. These publications provide pilot investigations and fundamental information to understand the value of these wealthy biodiversity and culture for medicinal plants in Myanmar.…”
Section: Introductionmentioning
confidence: 99%
“…The custom of herbal sauce or chutney formation was not very common throughout the region. Mentha longifolia (40), Mentha royleana (34), Cuminum cyminum (21), Zanthoxylum armatum (37), Allium ampeloprasum (14), and Thymus linearis (7) are the species used in chutney or sauce formation. Interestingly, all these species are aromatic in nature and used in fresh and dried form as well.…”
Section: Sauce or Chutneysmentioning
confidence: 99%
“…Ecosystems in the tribal belt is varied and comprise fields, forests and pastures; give rise to variety of wild fruits and vegetables [3]. These WFPs are not only important from nutritional point of view but also have important medicinal values [4,5] some of which have been evaluated for its pharmacological screening in many other parts of the world [5][6][7]. In current era, number of WFPs are being identified as "functional foods".…”
Section: Introductionmentioning
confidence: 99%
“…Some uses are published in ancient medicinal encyclopedias compiled by monks who tend to be the holders and transmitters of traditional religious knowledge [14,16,17]. However, formal records and studies on the traditional uses of figs among Myanmar's diverse ethnic groups are limited, and only a few formal medicinal or nutritional studies have been performed to describe the medicinal plants or to verify reported uses [18,19]. We hypothesized that these traditional uses often have accompanying conservation practices which may offer clues to help guide Myanmar in generating policy for sustainable development.…”
Section: Introductionmentioning
confidence: 99%